Tindak Tutur komisif dalam debat publik pertama calon bupati dan calon wakil bupati Mojokerto pada pilkada tahun 2024 - Ummah, Maslakhatu Nurul; Susanto, Gatut; Martutik, Martutik; Wahyu P., Gigih Caesar (Universitas Mulawarman, 2025)
The objectives of this study are (1) to describe the form of commissive speech acts in the first public debate of Mojokerto regent and vice-regent candidates; (2) to describe the purpose and context of commissive speech acts in the first public debate of Mojokerto regent and vice-regent candidates The method applied in this research is descriptive qualitative with a pragmatic approach. The data sources in this study are video transcripts of the first public debate of candidates for regent and vice-regent of Mojokerto in the form of words, phrases, or sentences. The debate theme was ‘Regional development strategy in realizing the welfare of the people of Mojokerto Regency.’ The results of this study found 22 commissive speech acts divided into four types: 14 speech acts of promise, 5 speech acts of intention, 3 speech acts of offer, and 1 speech act of refusal. According to the analysis that has been done, it is found that there are messages from both pairs of candidates and their implications that can be a reference for voters in making their choices in the 2024 regional head election.